Gambaran Tingkat Pengetahuan, Sikap Dan Tindakan Atas Kepemilikan Sanitasi Dasar Di Desa Pusong Kecamatan Banda Sakti - Shidqi, Hafizh; Khairunnisa, Cut; Nadira, Cut Sidrah (Jurnal Ilmiah Manusia Dan Kesehatan, 2025)
Basic sanitation in Pusong Village, Banda Sakti Subdistrict is a basic human need and is also the most determining factor in public health. The purpose of this study is to find out an overview of the level of knowledge, attitudes and actions of the head of the family on the ownership of basic sanitation. This research is descriptive research with cross-sectional method, with respondents are the Head of Family in Pusong Village, Banda Sakti Subdistrict as many as 72 Family Heads and data retrieval using questionnaires. The results showed that 65.3% of respondents had poor knowledge, 47.2% of respondents had enough attitude, and 68.1% of respondents had poor actions. Basic sanitation conditions in the community in Pusong Village Banda Sakti Subdistrict for clean water facilities, stool / latrine disposal facilities, landfill facilities, and wastewater disposal facilities as a whole are predominantly ineligible. The economic condition of the respondent causes a low level of knowledge, attitudes and actions of the respondent to be able to realize basic sanitary conditions that meet health requirements. The conclusion of this study is that most of the Family Heads in Pusong Village, Banda Sakti Subdistrict have poor knowledge, adequate attitude and poor actions on basic sanitation ownership. It is recommended to the public to take more concrete action in achieving the implementation of basic sanitation facilities through mutual assistance, and to the Lhokseumawe City Health Office and Related Agencies to further improve health education and promotion.